A história afro-brasileira pós-abolição em livros didáticos - Luciano Magela Roza (2014)
The study has as a central concern to analyze the approaches of afro-brazilian history in the context of the post-abolition, appropriated as curriculum content in textbooks produced after the publication of the Law Nº 10.639 / 03. This legislation, in opposition and combat to the production and circulation of subaltern representations, as well as the historical erasure of individuals and groups of ethnic-racial belonging of african origin, presuppose a repositioning of blacks in the history of Brazil. This reposition will give by the no- forgetfulness of their actions, presence and contributions and, therefore, should be remembered, and also by the proposition of positive representations about this historical subjects. The object of analysis are the teaching collections approved and reprinted in the National Program of the Textbook in 2008 and 2011, that have as investigative focus the explicit content suggested to the teaching-learning of the topic in question, present in the student book. Thus, the object is inserted in the interweaving of the following fields of study: History Teaching, the Textbook History and the Afro-Brazilian History. Considering the complexity of the object, the theoretical-methodological perspective adopted intends to associate assumptions and procedures of the qualitative researches, talking with other fields, notably, the History of School Disciplines and Social History of the Curriculum, Curriculum Studies, Cultural and Post-Colonial Studies, the production about the History Teaching and the Historiography and, especially, the production about the afro-brazilian history in the post-abolition. The research has shown that school configuration about afro-brazilian history, in the context of post-abolition, in the textbooks, has been developed through the diversity of appropriations, uses of the past and functions assigned to this content, proving to be a territory of broad ethical, political and cultural meaning.